Removal of Aliphatic Hydrocarbons from Gas Oil Contaminated Clay Soil via Soil Vapor Extraction - Hossein Nematollahi; Nasim Moradi; Morteza RiyaziNejad; Hossein Vahidi (Salehan Institute of Higher Education, 2018)
In this research, the performance of soil vapor extraction (SVE) for the removal of aliphatic hydrocarbons from gas oil contaminated soil and the effect of soil type on this method is studied. To explore the effect of soil type in the removal of hydrocarbons, SVE tests were conducted on 3 types of soil: 1) fine sand, 2) fine sand with 20% of kaolinite clay and 3) fine sand with 40% of kaolinite clay. Three extraction periods of 8, 16 and 24 hours were used. The results have shown that the efficiency of this method exceeds 78% in the removal of all hydrocarbons from fine sand, while an increase in clay significantly decreases the efficiency. Accordingly, the efficiency of this method decreases by 53.1% and 54.6% in fine sand with 20% of clay and fine sand with 40% of clay respectively. Furthermore, the results show that the higher concentration of some heavy and medium hydrocarbon leads to the more increase in early hours of SVE process, which indicates the alteration of hydrocarbons into each other.